ORAL ANTIPLATELET THERAPY IN STROKE PREVENTION. MINIREVIEW - Kral, Michal; Herzig, Roman; Sanak, Daniel; Skoloudik, David; Vlachova, Ivanka; Bartkova, Andrea; Hlustik, Petr; Kovacik, Michal; Kanovsky, Petr (Biomedical papers, 2010)
Background: Antiplatelet therapy plays a crucial role in the primary and secondary prevention of noncardioembolic ischemic stroke / transient ischemic attacks (IS/TIA). Several antiplatelet agents are available. This review deals with the characteristics of particular antiplatelet agents as well as choice of antiplatelet treatment in various situations, based on the evidence and international recommendations.Methods: PubMed and Stroke Trials Registry on-line databases and the European Stroke Organisation Guidelines for Management of IS/TIA 2008 and update of the recommendations of the American Heart Association / American Stroke Association Council 2008 on Stroke were used.Results: Acetylsalicylic acid (ASA) is the only antiplatelet drug used in primary prevention, mainly to reduce the risk of myocardial infarction (MI), but also in women aged 45 years or more and in some patients with non-valvular atrial fibrillation to reduce risk of IS/TIA. In the secondary prevention of noncardioembolic IS/TIA, ASA in combination with long release dipyridamole (DIP) and clopidogrel (CLOP) alone are considered first choice therapies. The choice of the particular antiplatelet agent should be individualized according to the patient risk factor profiles and treatment tolerance. ASA alone or triflusal can be used alternatively in patients who cannot be treated with either ASA+DIP or CLOP. The use of indobufen should be considered only in patients in need of temporary interruption of the antiplatelet therapy. Ticlopidine (TIC) should not be newly introduced into the treatment. Currently, insufficient data are available on the use of cilostazol in IS/TIA prevention.
Keywords: Antiplatelet therapy/Ischemic stroke/Prevention